Implementasi Program Gerakan Intensif Membaca (GIM) pada Kelas Rendah di SDN 1 Watubelah - Muhammad Nabil Afis; Marwan Supriyanto; Pipih Hadistia; Muhammad Nurfaisal Sidik; Aslinda Aslinda; Hema Widiawati (Mathematics Education Study Program, 2025)
The basic skills that must be possessed by students are literacy and numeracy. SDN 1 Watubelah packs a literacy program by providing an Intensive Reading Movement. This study contains an explanation of the Reading Intensive Movement which is a program of SDN 1 Watubelah which is carried out by lower grade students who collaborate with (PMDS) Student Service at school. The method used is a qualitative method with a case study approach with interview, observation and documentation instruments. In the implementation of the intensive reading movement, it produces conclusions in the form of program evaluations and program impacts in the form of advantages, disadvantages or obstacles and student participation